Comparison of fetal echocardiogram with fetal cardiac autopsy findings in fetuses with congenital heart disease. (2nd December 2021) - Gao, Shuang; Han, Jiancheng; Yu, Shaomei; Guo, Yong; Ruan, Yanping; Fu, Yuwei; Hao, Xiaoyan; Wang, Xin; Wang, Siyu; Zhou, Xiaoxue; Shang, Jianfeng; Zhang, Ye; et al.
Abstract: Objective: Although studies have compared fetal echo results with autopsy findings, investigations that compared multiple categories of congenital heart disease (CHD) are lacking. This study, therefore, aimed to compare fetal echocardiographic diagnoses with cardiac autopsy findings and evaluate the diagnostic accuracy of fetal echocardiography (FE). Methods: One hundred seventy-one specimens from fetuses diagnosed with CHD were collected after termination of pregnancy, and fetal autopsies were performed. FE and autopsy diagnoses were compared and the degree of their correspondence was categorized as "complete agreement" (FE results were in accordance with autopsy findings), "minor discrepancies" (autopsies verified the main FE diagnoses but added and/or revised some minor information), or "discordance" (autopsy findings were different from the primary diagnoses of FE). Results: The "complete agreement" group accounted for 87.1% (149/171) of the total specimens. In 11.7% (20/171) of cases, autopsies disclosed new deformities and/or revised some echo results (minor discrepancies group). Minor abnormalities were frequently embodied in small septal defects and vascular malformations. A rare malformation of common pulmonary vein atresia was confirmed by autopsy in two fetuses, but both were misdiagnosed by FE (discordance group). Conclusions: Fetal echocardiographic diagnoses were mostly consistent with autopsy findings. The diagnostic discrepancies mainly consisted of rare cases and minor abnormalities missed or misdiagnosed by FE. Autopsies may help confirm, modify, or add information to prenatal echo results. They may also help sonographers have a better understanding of the anatomic structures of CHD, especially for rare lesions, which could further improve the diagnostic accuracy and integrity of FE.